2014
DOI: 10.5539/elt.v7n5p89
|View full text |Cite
|
Sign up to set email alerts
|

What Do Teachers Need to Support English Learners?

Abstract: This study explored K-8 teachers' perceptions of their preparation and the challenges they encountered in delivering instruction to culturally and linguistically diverse learners. Using a mixed method research design, data were collected through a web-based survey from teachers in the state of Michigan. Researchers used chi-square tests to investigate the relationship between teachers' preparation and their knowledge of their diverse learners' learning needs. Qualitative comments were examined, organized, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…During the academic year 2013-14, Michigan employed approximately 500 certified teachers to work with ELs, a ratio of about one teacher for every 176 ELs. However, most of these regular classroom teachers did not feel adequately equipped to meet the needs of ELs (Gomez & Diarrassouba, 2014;Hutchinson & Hadjioannou, 2012). In their mixed-methods case study about teacher perceptions of preparedness for teaching ELs, Hutchinson and Hadjioannou found that 65% of teachers did not feel prepared to teach ELs and only 22% said they tried to incorporate English as a second language (ESL) strategies into their instructional delivery.…”
Section: State Of Michigan Datamentioning
confidence: 99%
See 2 more Smart Citations
“…During the academic year 2013-14, Michigan employed approximately 500 certified teachers to work with ELs, a ratio of about one teacher for every 176 ELs. However, most of these regular classroom teachers did not feel adequately equipped to meet the needs of ELs (Gomez & Diarrassouba, 2014;Hutchinson & Hadjioannou, 2012). In their mixed-methods case study about teacher perceptions of preparedness for teaching ELs, Hutchinson and Hadjioannou found that 65% of teachers did not feel prepared to teach ELs and only 22% said they tried to incorporate English as a second language (ESL) strategies into their instructional delivery.…”
Section: State Of Michigan Datamentioning
confidence: 99%
“…Teacher preparation programs have often not provided their teacher candidates with the knowledge and skills allowing them to be effective professionals that can attend efficiently to the academic and learning needs of multiple audiences (Gomez & Diarrassouba, 2014). School districts, on the other hand, have been attempting to supply the needed knowledge and skills to these practitioners in the forms of professional development workshops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers relied upon PD opportunities such as graduate courses or single workshops to demonstrate teaching strategies for today's educational climate, however, these opportunities are currently insufficient to equip teachers with the necessary knowledge to educate ELL students properly (Khong & Saito, 2013). Professional development training can offer teachers ways to improve their self-efficacy and deepen their knowledge about ELL students (Tran, 2014), yet 57% of teachers reported needing additional training to offer sufficient instruction to ELL students (Gomez & Diarrassouba, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Much prior scholarship has examined teachers' attitudes about and feelings of preparedness to serve ELs (e.g. Durgunoglu and Hughes, 2010; Gomez and Diarrassouba, 2014; Rubinstein-Avila and Lee, 2014), and outlined the competencies teachers of ELs need to be effective (e.g. Bunch, 2013; Faltis et al , 2010; de Jong et al , 2013; Lucas and Villegas, 2011).…”
Section: Introductionmentioning
confidence: 99%